PROTOTYPE MONITORING ALAT ELEKTRONIK PADA MASJID NURUL AMIN LAHUMBUNG BERBASIS INTERNET OF THINGS - Ma’arif, Syamsul; Candra, Adi; Awal Nur, Muhammad (CV. LAJAGOE PUSTAKA, 2024)
This study aims to: (1) To make a prototype of monitoring electronic devices in nurul amin lahumbung mosque based on the internet of things. (2) To find out the implementation of the prototype monitoring of electronic devices in the nurul amin lahumbung mosque based on the internet of things. This research used the prototype (prototyping) method. The stages of making tools using prototypes are gathering needs, building prototypes, evaluating prototypes, coding systems, testing systems, evaluating systems, using systems. The results of this study indicate that: (1) Prototype monitoring of electronic devices at the Nurul Amin Lahumbung mosque based on the internet of things is designed or made using NodeMcu Esp8266, Relay, Dht11 Sensor, Dfmini Player, Speaker, Fan, Lamp, Android Smartphone, Blynk Application, Wifi and 5V Adapter. The Blynk application as a timer as well as media monitoring and the Blynk application can run on smartphone specifications of at least 1.5 GB RAM with Android version 10 and above. (2) Implementation of prototype monitoring of electronic devices at the Nurul Amin Lahumbung mosque based on the internet of things can turn on the sound automatically properly according to the specified time and notifications are displayed in the Blynk application. Can turn on the lights automatically well at dawn, maghrib and Isha prayers. Can turn on the fan / turn off the fan automatically properly where the fan will turn on when the temperature is above 25oC and the fan will turn off when the temperature is below 25oC.